Psychological Behavior of Frontline Medical Staff in the Use of Preventive Medication for COVID-19: A Cross-Sectional Study - Yu, Xiaoyan; Li, Yuxi; Tang, Li; Deng, Lu; Zhao, Yuxin; Zhao, Xianmei; Xu, Huilan; Zeng, Ming (Frontiers in Psychology, 2020)
Purpose To understand the current pandemic, levels of anxiety in frontline staff, and whether they have been using medication to prevent COVID-19. Methods Between January 10 and March 10, 2020, 290 frontline staff completed a questionnaire incorporating the Generalized Anxiety Disorder Scale 7 (GAD-7) to indicate their psychological behavior in the use of preventive medication. Results Of those who participated in the study, 77.6% used preventive medication, with 47.5, 40.9, and 11.6% using these as part of routine preventive treatment, to fight infection after it was contracted, and after occupational exposure, respectively. There was a statistically significant relationship between the anxiety scale scores and the frequency of medication use (P < 0.05). Comparative analyses revealed that the scores of those in the group taking medication after occupational exposure (to respiratory and blood-borne pathogens) were significantly different from other groups. The proportion of participants choosing Western medicine, traditional Chinese medicine, and integrated Chinese and Western medicine was 24.4, 28.0, and 47.6%, respectively. Additionally, the relationship between the anxiety scale scores and the three types of medication was statistically significant (P < 0.05), as was the difference between Western medicine and other groups. According to Multinomial logistic regression based on the adjustment to gender, age, educational level, marital status, current workplace, and profession, participants with moderate to severe anxiety, had higher odds (OR = 10.331, 95%CI:1.453–73.429) of using Western medicine than participants with no anxiety. Participants with moderate anxiety were 6.399 times more likely to use an integrated combination of traditional Chinese and Western medicine compared to those with no anxiety (OR = 6.399, 95%CI:1.007–40.658). Furthermore, those with mild anxiety were 2.656 times more likely to use integrated traditional Chinese and Western medicine than those with no anxiety (OR = 2.657, 95%CI:1.075–6.570). The probability that frontline medical staff with moderate anxiety took preventive medication after occupational exposure to COVID-19 was 8.066 times (OR = 8.066, 95%CI:1.043–62.353) higher than that of staff without anxiety. Discussion This study revealed that there was more anxiety among frontline medical staff who took medication after unexpected occupational exposure. There was less anxiety among those using an integrated course of Chinese and Western medicine than Western medicine alone. It was also observed that anxiety affects the types and frequency of the preventive medication taken. Frontline medical staff who suffer from anxiety are also more likely to use medication to prevent COVID-19.